Heat and mass transfer of Williamson nanofluid flow yield by an inclined Lorentz force over a nonlinear stretching sheet - Mair Khan; M.Y. Malik; T. Salahuddin; Arif. Hussian (Results in Physics, 2018)
The present analysis is devoted to explore the computational solution of the problem addressing the variable viscosity and inclined Lorentz force effects on Williamson nanofluid over a stretching sheet. Variable viscosity is assumed to vary as a linear function of temperature. The basic mathematical modelled problem i.e. system of PDE’s is converted nonlinear into ODE’s via applying suitable transformations. Computational solutions of the problem is also achieved via efficient numerical technique shooting. Characteristics of controlling parameters i.e. stretching index, inclined angle, Hartmann number, Weissenberg number, variable viscosity parameter, mixed convention parameter, Brownian motion parameter, Prandtl number, Lewis number, thermophoresis parameter and chemical reactive species on concentration, temperature and velocity gradient. Additionally, friction factor coefficient, Nusselt number and Sherwood number are describe with the help of graphics as well as tables verses flow controlling parameters. Keywords: Williamson nanofluid, Temperature depended viscosity, Inclined magnetic field, Mixed convection, Chemical reactive species, Variable viscosity, Shooting method